Antioxidant Effect of Ethanolic Extract of Propolis in Liver of L-NAME Treated Rats - Selamoglu, Z. S.; Ozdemir I.; Ciftci O.; Gulhan M.F.; Savci A. (Wroclaw University of Medicine, 2015)
Background: The blocking of nitric oxide synthase (NOS) activity may cause vasoconstriction with formation of reactive oxygen species. Propolis is a natural product collected from plants by honeybees. Propolis has biological and pharmacological properties. Objectives: This study was designed to investigate the effects of propolis on catalase (CAT) activity, nitric oxide (NO) and malondialdehyde (MDA) levels in the liver tissues of NOS inhibited rats by Nco-Nitro-L-arginine methyl ester (L-NAME). Material and Methods: Rats were given a NOS inhibitor (L-NAME, 40 mg/kg, intraperitoneally) for 15 days to provoke hypertension and propolis (200 mg/kg, by gavage) the last 5 of the 15 days. Results: Nitric oxide levels in the liver tissue of the rats given L-NAME significantly decreased (p < 0.01). That parameter did not significantly alter in the liver of rats treated with propolis compared to the control group. CAT activity and MDA levels in the liver of the rats administrated L-NAME significantly increased compared to the control group (p < 0.01). These parameters significantly decreased in the liver of the rats given L-NAME + propolis compared to the L-NAME group (p < 0.01). Conclusions: The present data shows that L-NAME in the liver may enhance oxidative stress via inhibited nitric oxide synthase. Our results also suggest that this effect is suppressed by the antioxidant properties of propolis in the liver tissue of NOS inhibited rats. © Copyright by Wroclaw Medical University.
PubMed ID: 25931353
Keywords: L-NAME; Liver; Oxidative stress; Propolis; Rat